Lake Balaton as an accessible tourism destination – the stakeholders’ perspectives - Medarić, Zorana; Sulyok, Judit; KardosSzilvia; GabručJanja (Hungarian Geographical Bulletin, 2021)
This paper discusses the situation in the emerging field of accessible tourism at the Lake Balaton destination. The main objective of the study was to explore the current situation of accessible tourism at Lake Balaton, focusing on the perspectives of tourism stakeholders. Various issues were reflected upon, such as: a) the “general” accessibility of the destination in terms of the current state of accessibility of the destination as well as the accessibility of information, transportation, accommodation, food and beverage services, tourist attractions, funds and know-how; b) factors that make the destination Lake Balaton competitive as an accessible destination; and c) general attitudes of tourism stakeholders towards accessible tourism. The research focus was on the destination itself, not on individual attractions or tourism service providers. In order to assess the current situation and future prospects for accessible tourism at Lake Balaton, an exploratory quantitative online survey among stakeholders was conducted between 5 September and 5 October 2020. A total of 39 stakeholders participated in the survey, including 11 local municipality stakeholders, 8 local destination management organisations, and 20 tourism service providers (accommodation, catering or attractions/sights). The results show that the Lake Balaton destination accessibility is currently at an early stage of development and tends to target groups with low accessibility needs. Among the factors of destination competitiveness for the accessible tourism market, supportive factors (e.g. accessibility, infrastructure, and the commitment of stakeholders) are ranked first, followed by resources and attractions (landscape, climate, activities, culture, history, tourism service providers, and events) and the quality factor (including value for money, safety, perception and image). Planning and management (including positioning and branding) is the lowest ranked factor even though such aspects are critical factors and foundations for the development of accessible tourism.